THAI AND BUDDHIST PRECEPT TOURISM DURING COVID-19 FOR LEARNING - Pipathananunth , Manus (ASEAN Journal of Religious and Cultural Research, 2020)
Thai and Buddhist Precept Tourism in during COVID-19 main purpose to study about Cultural traditions of Thai and Buddhist people focus on Concept of Tourism Management, Thai Scruple and Buddhist principles. For Thai way of Tourism Management which consists of: 1. Travel in Religious way 2. Travel in Creative and Traditional ways 3. Travel in Health, Beauty and Thai Traditional Doctor. 4. Travel in Ecosystem. Tourism essential elements which are Tourism providers, Tourists and Government agency.